Comparative genomics and functional analysis of rhamnose catabolic pathways and regulons in bacteria - Rodionova, Irina A.; Li, Xiaoqing; Thiel, Vera; Stolyar, Sergey; Fredrickson, James K.; Bryant, Donald A.; Osterman, Andrei L.; Best, Aaron A.; Rodionov, Dmitry A. (Frontiers in Microbiology, 2013)
L-rhamnose (L-Rha) is a deoxy-hexose sugar commonly found in nature. L-Rha catabolic pathways were previously characterized in various bacteria including Escherichia coli. Nevertheless, homology searches failed to recognize all the genes for the complete L-Rha utilization pathways in diverse microbial species involved in biomass decomposition. Moreover, the regulatory mechanisms of L-Rha catabolism have remained unclear in most species. A comparative genomics approach was used to reconstruct the L-Rha catabolic pathways and transcriptional regulons in the phyla Actinobacteria, Bacteroidetes, Chloroflexi, Firmicutes, Proteobacteria, and Thermotogae. The reconstructed pathways include multiple novel enzymes and transporters involved in the utilization of L-Rha and L-Rha-containing polymers. Large-scale regulon inference using bioinformatics revealed remarkable variations in transcriptional regulators for L-Rha utilization genes among bacteria. A novel bifunctional enzyme, L-rhamnulose-phosphate aldolase (RhaE) fused to L-lactaldehyde dehydrogenase (RhaW), which is not homologous to previously characterized L-Rha catabolic enzymes, was identified in diverse bacteria including Chloroflexi, Bacilli and Alphaproteobacteria. By using in vitro biochemical assays we validated both enzymatic activities of the purified recombinant RhaEW proteins from Chloroflexus aurantiacus and Bacillus subtilis. Another novel enzyme of the L-Rha catabolism, L-lactaldehyde reductase (RhaZ), was identified in Gammaproteobacteria and experimentally validated by in vitro enzymatic assays using the recombinant protein from Salmonella typhimurium. C. aurantiacus induced transcription of the predicted L-Rha utilization genes when L-Rha was present in the growth medium and consumed L-Rha from the medium. This study provided comprehensive insights to L-Rha catabolism and its regulation in diverse Bacteria.